การจัดการความเสี่ยงด้านการบริหารงานบุคคลขององค์การบริหารส่วนตำบลโพธิ์ไทร อำเภอพิบูลมังสาหาร จังหวัดอุบลราชธานี - พวงจินดา ทิพเนตร; ฤทธิรอด ธีระ (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2016)
การศึกษาอิสระครั้งนี้มีวัตถุประสงค์เพื่อศึกษาสภาพความเสี่ยงด้านการบริหารงานบุคคลและศึกษาแนวทางในการจัดการความเสี่ยงด้านการบริหางานบุคคลขององค์การบริหารส่วนตำบลโพธิ์ไทร อำเภอพิบูลมังสาหาร จังหวัดอุบลราชธานี โดยเก็บรวบรวมข้อมูลด้วยการสัมภาษณ์เชิงลึก จากกลุ่มเป้าหมายในการศึกษา จำนวน 7 คน ประกอบด้วย นายกองค์การบริหารส่วนตำบล ปลัดองค์การบริหารส่วนตำบล รองปลัดองค์การบริหารส่วนตำบล หัวหน้าสำนักปลัด ผู้อำนวยการกองคลัง ผู้อำนวยการกองช่าง และหัวหน้าส่วนการศึกษาศาสนาและวัฒนธรรมแล้ววิเคราะห์เชิงพรรณนาเพื่อสรุปประเด็นสำคัญตามวัตถุประสงค์ ผลการศึกษา พบว่า องค์การบริหารส่วนตำบลโพธิ์ไทรมีความเสี่ยงในการบริหารงานบุคคล ด้านการสรรหาซึ่งประสบปัญหาในการสอบแข่งขันพนักงานจ้าง โดยมีระบบอุปถัมภ์เข้ามาแทรกแซงในกระบวนการสรรหา กระบวนการสรรหาไม่รัดกุม ด้านการโอนย้ายพบปัญหาของกระบวนการโอนย้ายที่มีความล่าช้า ระเบียบกฎหมาย ให้อำนาจกับฝ่ายการเมืองมากเกินไป และไม่มีระบบอุทธรณ์ในการโยกย้าย ด้านการเลื่อนขั้นเงินเดือน พบการแทรกแซงกระบวนการประเมินเพื่อเลื่อนขั้นเงินเดือนจากกลุ่มผลประโยชน์ต่างๆ ด้านการพัฒนาบุคลากรเกิดปัญหาการขาดแคลนงบประมาณ สำหรับนำไปใช้ในการพัฒนาบุคลากรและองค์กรไม่มีกระบวนการแลกเปลี่ยนเรียนรู้ในการทำงาน แนวทางในการบริหารจัดการความเสี่ยงด้านการบริหารงานบุคคล ควรดำเนินการสรรหาตามระบบคุณธรรมให้เป็นไปตามหลักความรู้ความสามารถ ไม่ควรให้กลุ่มผลประโยชน์เข้ามาแทรกแซง ควรปฐมนิเทศให้ความรู้กับพนักงานใหม่ทุกครั้ง ควรมีระบบการอุทธรณ์กรณีเกิดการโอนย้ายที่ไม่เป็นธรรม จัดตั้งหน่วยงานกลางระดับจังหวัดให้มีอำนาจอนุมัติการโอนย้ายโดยมีอำนาจเทียบเท่านายกองค์การบริหารส่วนตำบล นำหลักการประเมินแบบ 360 องศาและระบบอุทธรณ์เข้ามาใช้กับกระบวนการเลื่อนขั้นเงินเดือน และควรจัดทำแผนปฏิบัติการ เพื่อพัฒนาบุคลากร สนับสนุนงบประมาณ ในการดำเนินการเพื่อพัฒนาบุคลากร Risk management in human resource management of Phosai Subdistrict Administration Organization Phibunmangsahan District, Ubonratchathani Province The objective of this research were to study the risk management in human resource management and to study the approach of risk management in human resource management of Pho Sai Sub-District Administration Organization, Phibun Mangsahan District, Ubon Ratchathani Province. The data collection was depth-interview from sample group which consisted of 7 persons including executive, Chief Administrator of the SAO, Duputy Chief Administrator of the SAO, Chief of the Office of the SAO Chief Administrator, the director of the Treasury, Division engineer, Chief of the Subdivision of Education Religious and Culture Promotion, this study was descriptive analysis and the conclusion was conducted according to the objectives. From the research, it was found that the Pho Sai SAO had the risk management relating the recruiting, the problem was the job-application test of employee was intervened by patronage system, this is because the recruiting system was not concisely and when considered in job transfer, it was found that the job transfer process was quite lately, law gave the authority to political sector too much and there were not the appeal and compliant system for transfer, as for promotion, it was found that the job promotion was intervened by various benefit group, as for personal development, it was found that it lacked of budget for developing the personal and the organization was not the job rotation for learning exchange. The approaches for risk management in human resource management should recruit the employee with merit system consistent with the knowledge and capability, it should not allow the benefit group intervening in the process, it should always hold the orientation to new employee, the appeal and compliant system should be supported in case of unfair job transfer, provincial neutral center should be established and gave it authority and power to approve the job transfer and its authority should be equal to Chief executive SAO, it should use the 360 degree feedback and appeal and compliant system in the job promotion and it also should develop personal according to personal development plan, the budget of personal development should be supported seriously and it should promote the knowledge exchange during performance.